Natural Language Processing for Everyone: The Case for a Centralized Icelandic NLP Platform. - Hafsteinsson, Hinrik; Steingrímsson, Steinþór (Digital Humanities in the Nordic & Baltic Countries Publications (DHNB Publications), 2025)
This paper presents the Árni Magnússon Institute's NLP platform, a website where the functionality of important language technology tools for Icelandic is made accessible to the general public, both through a user interface and a standardized API. The platform is presented as a solution to the problem that even though a specific language technology tool exists, it does not go without saying that anyone can use it: A certain technical know-how is almost always a prerequisite for being able to use these tools. The platform is presented with the following NLP solutions integrated: Tokenization, PoS-tagging, Lemmatization and Hyphenation, with more tools becoming available pending future development. The platform is now made available to the public, with the caveats of it being in active development and undergoing regular changes.